Semantically Based Clinical TCM Telemedicine Systems - Wong, A.K.Y (Springer, 2015)
Recent years have seen the development of two significant trends namely: the adoption of some Traditional Chinese Medicine Practices into mainstream Allopathic Western Medicine and the advent of the internet and broad band networks leading to an increased interest in the use of Telemedicine to deliver medical services.